Home country economic, political, social push factors and intention to migrate in Iraq: psychological distress as mediator - Yousif Mousa Sabti; Subramaniam Sri Ramalu (Cogent Business & Management, 2024)
The migration of talents from one country to another has become a growing concern worldwide. It has been argued that the home country's economic, political, and social push factors drive the intention to migrate among its talents. This study aims to investigate the direct and indirect effects of home country's economic (financial difficulties, economic instability), political (political instability, corruption), and social (life dissatisfaction, problems of family well-being) push factors on the intention to migrate among medical doctors in Iraq. The indirect effect involves testing the mediating effect of psychological distress in the proposed relationships. This study uses a cross-sectional research design to gather data from a sample of 460 medical doctors working in private and public hospitals in Iraq. The Partial Least Square (PLS) two-step path modelling was used to test the direct and indirect hypotheses. The findings of this study show that financial difficulties and economic instability has a positive direct effect on the intention to migrate. However, the direct effect of political instability, corruption, life dissatisfaction, and problems of family well-being on the intention to migrate is insignificant. Additionally, the direct positive effect of financial difficulties, economic instability, political instability, and corruption on psychological distress is significant. Likewise, the effect of problem of family well-being on psychological distress is also significant, while the effect of life dissatisfaction on psychological distress is not significant. Further, the direct positive effect of psychological distress on intention to migrate is significant. A full mediation effect of psychological distress was found in the relationship between financial difficulties, economic instability, political instability, corruption, problem of family well-being and intention to migrate. The relationships examined in this study offer new directions in the study of migration among talents, specifically among the medical doctors in Iraq. The findings can be used by human resource managers, government agencies, and policymakers to improve the psychological state of medical professionals in Iraq hospitals.
Keywords: 650; Talents; economics factors; political factors; social factors; corruption; economic instability; financial difficulties; problems of family well-being; life dissatisfaction; political instability; psychological distress; intention to migrate